2010
DOI: 10.5539/ijef.v2n4p3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Industry Trade and Labour Market Adjustment in the Automobile Industry

Abstract: This paper examines the effects of increased intra-industry trade on the labour market adjustment costs in Portugal's automobile industry. Using a static and dynamic panel data approach, the results show a negative correlation between changes of employment and marginal intra-industry trade. These results confirm the smooth adjustment hypothesis, as well as suggesting that the multinational companies (MNC) engaged in the automobile sector have low adjustment costs if they increase the intra-firm trade, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 12 publications
4
20
0
1
Order By: Relevance
“…puede inducir a una reducción de mano de obra y por lo tanto a que se desplacen los individuos a otros sectores económicos, es decir que se presenta una relocalización de mano de obra y por lo tanto mayores costos de ajuste (Brülhart y Thorpe 2000;Ferto 2009;Faustino 2010;Rasekhi y Ghaderi, 2012). Segundo, el aumento de la productividad sectorial ( )…”
Section: Resultados Econométricosunclassified
“…puede inducir a una reducción de mano de obra y por lo tanto a que se desplacen los individuos a otros sectores económicos, es decir que se presenta una relocalización de mano de obra y por lo tanto mayores costos de ajuste (Brülhart y Thorpe 2000;Ferto 2009;Faustino 2010;Rasekhi y Ghaderi, 2012). Segundo, el aumento de la productividad sectorial ( )…”
Section: Resultados Econométricosunclassified
“…H6: Wages tend to decrease when employment increases. Greenaway et al (2020), Faustino and Leitão (2012) and Aggarwal and Chakraborty (2020) consider a negative sign between wages and employment changes (β 6 LogΔWages<0).…”
Section: Methodology and Econometric Strategymentioning
confidence: 99%
“…When we achieved a meta-analysis, we observed that two types of empirical studies were developed: static models, where the authors did not use the lagged variable of employment changes (Cabral and Silva 2006;Brülhart et al 2006;White and Chen 2012;Rasekhi and Ghaderi 2012); and the second type of studies where the authors used the lagged variable of employment (Aggarwal and Chakraborty 2020;Erlat and Erlat 2006;Faustino 2010;Faustino and Leitão 2012;Pinto et al 2019;Thorpe and Leitão 2012). Furthermore, it should be referred that not all studies confirm the hypothesis SAH (smooth adjustment hypothesis).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations